2012
DOI: 10.1158/0008-5472.can-11-3909
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Resensitization to Platinum in Ovarian Cancer

Abstract: Preclinical studies have shown that hypomethylating agents reverse platinum resistance in ovarian cancer. In this phase II clinical trial, based upon the results of our phase I dose defining study, we tested the clinical and biologic activity of low-dose decitabine administered before carboplatin in platinum-resistant ovarian cancer patients. Among 17 patients with heavily pretreated and platinum-resistant ovarian cancer, the regimen induced a 35% objective response rate (RR) and progression-free survival (PFS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
304
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(321 citation statements)
references
References 52 publications
14
304
2
1
Order By: Relevance
“…Treatment with 5-aza-2 0 -deoxycytidine restores sensitivity to carboplatin in patients with advanced ovarian cancer. 41 In addition, it has been demonstrated that defective multidrug resistance proteins lead to platinum resistance. 42 Defects in N-glycosylation also may affect tumor growth in cells with deregulated phosphatidylinositol 3-kinase/v-Akt murine thymoma viral oncogene homolog (PI3K-Akt) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 5-aza-2 0 -deoxycytidine restores sensitivity to carboplatin in patients with advanced ovarian cancer. 41 In addition, it has been demonstrated that defective multidrug resistance proteins lead to platinum resistance. 42 Defects in N-glycosylation also may affect tumor growth in cells with deregulated phosphatidylinositol 3-kinase/v-Akt murine thymoma viral oncogene homolog (PI3K-Akt) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methyltransferase inhibitors (DNMTis), such as 5-azacytidine (Aza) and 5-aza-2'-deoxycytidine (Dac) are effective cancer therapies in hematologic neoplasms (Tsai et al, 2012) (Matei et al, 2012) and are FDA approved for the pre-leukemic disorder myelodysplasia (MDS) (Kaminskas et al, 2005). These cytidine analogues incorporate into DNA, block catalytic actions of DNA methyltransferases (DNMTs), and trigger their degradation (Stresemann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MLH1 promoter hypermethylation has been reported in numerous types of tumors, including colorectal (33), gastric cancer (34) and EC (35). Previous studies have also reported that MLH1 hypermethylation may be associated with poor prognosis for patients with gastric (22), ovarian (36) and colorectal cancer (37), whilst studies on the prognostic value of MLH1 methylation in Han Chinese patients with EC or ESCC are scarce. The present study demonstrated that MLH1 promoter hypermethylation is a prognostic marker of ESCC in Chinese males.…”
Section: Discussionmentioning
confidence: 99%